H/D exchange and mass spectrometry in the studies of protein conformation and dynamics: Is there a need for a top-down approach? - Kaltashov, Igor A. (2009)
Hydrogen/deuterium exchange (HDX) combined with mass spectrometry (MS) detection has matured in recent years to become a powerful tool in structural biology and biophysics. Several limitations of this technique can and will be addressed by tapping into ever expanding arsenal of methods to manipulate ions in the gas phase offered by mass spectrometry.